2021
DOI: 10.4081/jphr.2021.1971
|View full text |Cite
|
Sign up to set email alerts
|

Turnover among Foreign Nurses in Saudi Arabia

Abstract: Background: Globally, nursing turnover has become a contemporary concern that significantly influences the financial proficiency of healthcare systems. Not only costs, but healthcare accessibility and quality also reverberate the consequence of the phenomenon.Design and methods:  The study explores the factors that attribute to turnover among foreign registered nurses working in Saudi Arabia. A quantitative-based cross-sectional descriptive study design that uses survey data to make statistical inferences abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“… 8 Quick turnover among nurses is attributed to, but not limited to the staff scarcity, arduous mental/physical labour, job dissatisfaction, poor recognition, and international job opportunities. 9 , 10 From the National Health Workforce Account (NHWA) 2018, India has 5.76 million HW, of which 2.34 million are nurses/midwives. However, only 1.40 million nurses/midwives comprised the active HW size estimated from the Periodic Labour Force Survey 2017–2018 by the National Sample Survey Office (NSSO).…”
Section: Introductionmentioning
confidence: 99%
“… 8 Quick turnover among nurses is attributed to, but not limited to the staff scarcity, arduous mental/physical labour, job dissatisfaction, poor recognition, and international job opportunities. 9 , 10 From the National Health Workforce Account (NHWA) 2018, India has 5.76 million HW, of which 2.34 million are nurses/midwives. However, only 1.40 million nurses/midwives comprised the active HW size estimated from the Periodic Labour Force Survey 2017–2018 by the National Sample Survey Office (NSSO).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, current literature data show that nurses' intention to leave is influenced by their quality of life, including physical and psychological health. Additional reasons for leaving specifically among international nurses were low salary, work‐related stress, burnout, unfair and unequal remuneration offered to nurses, psychological factors associated with the employer (Albougami et al, 2020; Alreshidi et al, 2021; Batayneh et al, 2019). In addition, work hours, social stigma towards nurses, career advancement opportunities and the desire to continue higher education or improve skills to influence nurses' decision to leave the organization.…”
Section: Introductionmentioning
confidence: 99%
“…21 (43.8%) articles revealed that professional vision towards nurses, lack of social support, work overload and low‐level job satisfaction are factors that cause staff turnover (Adams et al, 2021 ; Aeschbacher & Addor, 2018 ; Aiyub et al, 2013 ; Alameddine et al, 2017 ; Alshmemri et al, 2013 ; Chan et al, 2013 ; Drennan & Ross, 2019 ; Gray et al, 2018 ; Heijden et al, 2019 ; Hung & Lam, 2020 ; Ke & Stocker, 2019 ; Leineweber et al, 2016 ; Liu et al, 2018 ; Masenyani et al, 2018 ; Nantsupawat et al, 2017 ; Purohit & Vasava, 2017 ; Sirisub et al, 2019 ; Uthaman et al, 2016 ; Varasteh et al, 2021 ; Yahyaei et al, 2022 ; Yang et al, 2017 ). Another 10 (20.83%) articles confirmed that poor salaries or no changes to salary and poor working conditions are some of the contributing factors to nurses' turnover (Alameddine et al, 2017 ; Alreshidi et al, 2021 ; Chan et al, 2013 ; Hudgins, 2016 ; Kakemam et al, 2019 ; Marufu et al, 2021 ; Mehdaova, 2017 ; Park & Yu, 2019 ; Sirisub et al, 2019 ; Souza et al, 2017 ) and four (8.3%) articles confirmed that older nurses left work before their retirement age due to health conditions and limitation on new technology by older nurses are factors causing turnover (Buchan et al, 2015 ; Kurjenluoma et al, 2017 ; Sirisub et al, 2019 ; Uthaman et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…Ten (20.83%) articles revealed that ineffective policies regulations and strategies, poor policy (Alameddine et al, 2017 ; Drennan & Ross, 2019 ; Seitovirta et al, 2017 ), poor planning and human resource planning, inadequate workforce planning and recruitment (Alreshidi et al, 2021 ; Aluko et al, 2019 ; Batran, 2019 ; Marć et al, 2019 ; Marufu et al, 2021 ; Purohit & Vasava, 2017 ), incompetent implementation plan and continue change of government officers (Park & Yu, 2019 ; Yun et al, 2010 ) and lack of leadership management (Souza et al, 2017 ) were main factors affecting shortage in nursing workforce. Furthermore, 7 (14.6%) articles supported that increased workload (Batran, 2019 ; Hudgins, 2016 ), unattractive working conditions, poor working conditions (Hung & Lam, 2020 ; Kakemam et al, 2019 ; Nantsupawat et al, 2017 ) and inadequate support affects nursing shortage and nurses' turnover (Alshmemri et al, 2013 ; Chan et al, 2013 ; Mehdaova, 2017 ).…”
Section: Resultsmentioning
confidence: 99%